Evaluation of Synergistic Effect of Kaempferia galanga L. Rhizome Extracts on the Antibiotic Activity Antibiotics against Bacterial Pathogens - Almira Fahrinda; Sjarif Ismail; Khemasili Kosala; Ika Fikriah; Yuniati Yuniati (Journal of Tropical Pharmacy and Chemistry, 2018)
Background: aromatic ginger rhizome (Kaempferia galanga L.) is a member of Zingiberaceae family, has been known to have an antibacterial effect is used for everyday cooking spices, but the synergistic effect on broad spectrum antibiotics was unknown. Objective: this research was conducted to find out the synergistic effect of Kaempferia galanga L. Rhizome extract (KGR) on some broad-spectrum antibiotics against gram positive and negative bacterial pathogens in vitro. Method: KGR was taken from farmers in Samarinda City, East Kalimantan Province, Indonesia. Extraction by maceration with ethanol solvent. Antibacterial activity test of KGR ethanol extract, antibiotic and synergistic effect using Mueller-Hinton agar, Kirby-Bauer disc diffusion method on ampicillin, cefuroxime, chloramphenicol, ciprofloxacin, and meropenem antibiotics against Staphylococcus aureus and Escherichia coli. Results were expressed in percentage increase of the inhibition zone. Statistical test with t-test, significantly different if p<0.05. Results: KGR ethanol extract showed increase the percentage of antibiotic inhibition zone, ampicillin being the highest and the weakest of ciprofloxacin in E. coli; meropenem being the highest and the weakest of ciprofloxacin in S. aureus, statistically significant different tests on antibiotic ampicillin (E. coli), meropenem and cefuroxime. Conclusion: KGR ethanol extract showed synergistic effect on antibiotic ampicillin (E. coli), meropenem and cefuroxime in S. aureus and E. coli.